Diagnostic accuracy of the use of parental‐reported sleep bruxism in a polysomnographic study in children. Issue 5 (9th September 2016) - Restrepo, Claudia; Manfredini, Daniele; Castrillon, Eduardo; Svensson, Peter; Santamaria, Adriana; Alvarez, Claudia; Manrique, Ruben; Lobbezoo, Frank
Abstract : Background: Polysomnography (PSG) is the gold standard for sleep bruxism (SB) diagnosis. PSG/SB children's criteria are not available; thus, parental‐report SB is widely used. Aim: Assessing the diagnostic accuracy of parental report of sleep tooth grinding (STG) with a PSG/SB diagnosis in children, adopting adult criteria. Design: Thirty‐seven children from clinics of Universidad CES were included. Parents filled the Children's Sleep Habits Questionnaire (CSHQ) assessing the single‐observation report – CSHQ – of STG with a No/Yes answer and five ordinal answers. A 5‐day diary reporting the presence/absence of STG (multiple‐observation report) was also completed. Each child underwent a single‐night PSG study. Sensitivity, specificity, positive predictive value, negative predictive value, accuracy, likelihood ratios, Spearman correlation coefficient, and Cohen's kappa coefficient were used to analyze data. Results: Single observation, using No/Yes answer, showed acceptable specificity and NPV, while low PPV and sensitivity. Accuracy and likelihood ratios were low. When using the five ordinal answers, weak correlation and fair agreement ( r = 0.34 and κ = 0.40) with PSG/SB adult criteria were found. Multiple‐observation evaluation of STG presented moderate correlation and agreement ( r = 0.50 and κ = 0.48). Conclusions: Although multiple‐observation report achieved better agreement than single‐observation report, our results failed supporting the validity of report strategies for the diagnosis of SB in children, as an equivalent of PSG/SB adult criteria.